TEACHING VOCABULARY USING REALIA AND USING WORD CARD TO THE TENTH GRADE STUDENTS OF MA AL-FAIZIN BANGSRI JEPARA - Ummi Hidayatun Nikmah (Universitas PGRI Semarang, 2014)
The aims of this research are: (1) to what extent is the students’ vocabulary mastery taught using realia, (2) to what extent is the students’ vocabulary mastery taught using word card, and (3) is there any difference in vocabulary mastery between the students taught using realia and those taught using word card.In this research the writer used experimental quantitative research. The population of this research consists of 150 students. The sample of this reserach class X.1 used realia and class X.2 used word card. The instrument of the research was test.According to the calculation, the result showed that t-test obtained > t-table. The result obtained 1,84 in significance 5% with db = 29. It was consulted into t-table in significance level 0,95, t test (1,84) is higher than ttable (0,95). It means that there is a significant difference between teaching vocabulary using realia and word card of the tenth grade students of MA Al-Faizin Bangsri Jepara. The sudents taught realia class have big influence than the students taught using word card because using realia made the students more interest and easy to understand in teaching vocabulary mastery process